2016
DOI: 10.18632/oncotarget.8518
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic miRNA and meta-signature miRNAs involved in human adipocyte differentiation and obesity

Abstract: MicroRNAs (miRNAs) have been identified as a new class of regulatory molecules that influence many biological functions, including metabolism, adipocyte differentiation. To determine the role of adipogenic miRNAs in the adipocyte differentiation process, we used microarray technology to monitor miRNA levels in human adipose-derived mesenchymal stem cells (hMSCs-Ad), human stromal vascular cells (SVCs) and differentiated adipocytes. 79 miRNAs were found to be differentially expressed, most of which are located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 34 publications
0
78
0
1
Order By: Relevance
“…More complete understanding of fat deposition mechanism is vital for beef cattle breeding and beef production. MicroRNAs are important post-transcriptional molecules regulating adipogenesis and lipid accumulation as previously discovered35. However, their precise roles of miRNAs in bovine fat deposition are far from clear.…”
Section: Discussionmentioning
confidence: 99%
“…More complete understanding of fat deposition mechanism is vital for beef cattle breeding and beef production. MicroRNAs are important post-transcriptional molecules regulating adipogenesis and lipid accumulation as previously discovered35. However, their precise roles of miRNAs in bovine fat deposition are far from clear.…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction of miRNAs has been associated with a large number of diseases. For instance, the importance of miR-21 in different types of diabetes mellitus has been described by Sekar et al [8], and the miRNAs of the hsa-let-7 family and others are associated with obesity and related metabolic diseases [9]. miRNAs also participate in arthritic diseases [10], kidney disease [11], cardiovascular diseases [12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-346 regulates hBMSCs osteoblast differentiation by targeting GSK-3β and activating the Wnt/β-catenin pathway [31]. Moreover, miR-27b has been verified to participate in lipid metabolism and adipogenesis [32,33], which is important for revealing these mechanisms and finding treatments for obesity, diabetes mellitus, and other obesity related metabolic diseases. In our study, we identified that miR-27b expression was significantly lower during adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%